A Systematic Literature Review on Local Wisdom Actualization in Character Education to Face the Disruption Era - Muhamad Parhan; Dimas Febriansyah Krisna Dwiputra (Journal of Innovation in Educational and Cultural Research, 2023)
Previous studies reveal that Indonesia faces character problems of the young generation. These problems can be addressed by utilizing local wisdom. Nevertheless, comprehensive studies on optimizing local wisdom in character education are limited. Accordingly, this study is conducted to overcome this gap. Thus, the research objectives are to analyze the scope of using local wisdom in education and to investigate the form of local wisdom-based character education at schools. This study employed the PRISMA 2020 systematic literature review method, utilizing Scopus and Google Scholar as databases. A total of 88 articles were collected, but only 18 met the criteria for thematic-qualitative analysis. This study finds that the use of local wisdom in character education can be implemented not only within schools but also within families and communities. Meanwhile, its utilization can be done in the form of learning about local wisdom, learning with local wisdom, learning through local wisdom, and learning to be wise. In conclusion, this study's academic contribution enhances the contextual, diverse, and comprehensive nature of character education. It serves as a valuable reference for stakeholders in developing and implementing local wisdom-based character education, fostering an adaptable, wise, and responsible young generation in the face of the disruptive era.